PENGEMBANGAN BAHAN AJAR BERBANTUAN APLIKASI NEARPOD PADA MATERI ADA HEWAN APA SAJA DISEKITARMU DI SEKOLAH DASAR - Alda Florencia; Griet Helena Laihad; Santa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research method uses the Research and Development (R&D) method with the ADDI (analysis, design, development, implementation) development model. This research involved 25 students and in the process of validation and trial teaching materials that had been developed. Validation was carried out by three experts, namely media experts, linguists and material experts, with media expert validation results of 93%, linguist validation results of 100%, and material expert validation results of 92%, with an average result of 95% which is included in the